Height as a sign of power: the patrimonial values of the headquarters of the Banco de Credito in Piura from the perspective of its community - Morocho Gago, Laura (2025)
The values attributable to an object are not static or embedded in it, but associated with it by the perception of individuals who recognize its value. The objective of the present investigation is to determine the symbolic, formal and use values based on the classification of Dr. Cristina Nieto Pérez (2018), recognizable at present, to the headquarters building of the Banco de Crédito del Perú located in the old center of the city of Piura, from the perception of the Piura community; and the opinions of specialists, experts and institutions. This is a non-experimental, mixed-focus, descriptive-design investigation. Through instruments such as surveys, interviews, and analysis sheets, the heritage values recognizable by the heritage subjects were identified, in order to contribute to their dissemination and recognition.